Fun Book : Ancient Greece - Ransford, Sandy; Farris, David, Illus (London : The British Museum Press, 1999)
The Greeks without grief! There's never a dull moment in this collection of brain-boggling games, word-searches, crosswords, number and picture puzzles all about Greece.
Keywords: Crosswords -- Greece -- Ancient; Puzzles -- Greece -- Ancient; Ancient Greece -- Civilizations